2005
DOI: 10.1007/s10681-005-2910-7
|View full text |Cite
|
Sign up to set email alerts
|

Induction of 2n pollen in tulips by arresting the meiotic process with nitrous oxide gas

Abstract: Triploid tulips have agronomically desirable traits such as vigorous growth and large flower size, but only a portion of all cultivated tulips is triploid. To apply 2n pollen to polyploid breeding of tulips, the polyploidizing agent, nitrous oxide gas (N 2 O), was applied to bulbs. In tulips, meiosis in anthers occurs inside the bulbs from mid-to late-October. When meiosis in anthers (excised from bulbs) reached metaphase I, we treated other bulbs of the same clones with N 2 O for 24-48 h. Most of the treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 40 publications
(39 reference statements)
1
38
0
2
Order By: Relevance
“…Recently different attempts, with variable success, were made to induce these gametes in any genotype of interest. An overview of the methods used to induce 2n gametes is given in Dewitte et al, 2010b;Okazaki et al, 2005). N 2 O is suitable for treating organs inside tissues as the gas simply permeates the tissue, thereby protecting the tissues from harmful after-effects as soon as the gas is released (Kato & Geiger, 2002;Östergren, 1954).…”
Section: Induction Of 2n Gametesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently different attempts, with variable success, were made to induce these gametes in any genotype of interest. An overview of the methods used to induce 2n gametes is given in Dewitte et al, 2010b;Okazaki et al, 2005). N 2 O is suitable for treating organs inside tissues as the gas simply permeates the tissue, thereby protecting the tissues from harmful after-effects as soon as the gas is released (Kato & Geiger, 2002;Östergren, 1954).…”
Section: Induction Of 2n Gametesmentioning
confidence: 99%
“…Detailed studies on the exact mechanism of N 2 O mediated chromosome doubling during meiosis are also limited, but it has been suggested that N 2 O disrupts the spindle mechanism in both mitosis (Dvorak et al, 1973;Kato & Birchler, 2006;Kihari & Tsunewaki, 1960;Östergren, 1954) and meiosis (Akutsu et al, 2007;Barba-Gonzalez et al, 2006;Okazaki et al, 2005;). Consequently, aneuploidy is frequently reported after treatments.…”
Section: Induction Of 2n Gametesmentioning
confidence: 99%
“…In meiotic (sexual) polyploidisation, 2n gametes are induced (usually 2n pollen) by arresting the mitotic process. 2n pollen (induced with nitrous oxide gas) has recently been used for crossing with diploid cultivars in order to obtain triploids of tulip, lily, and begonia (Okazaki et al 2005;BarbaGonzalez et al 2006;Dewitte et al 2010). The natural sexual polyploids (mainly triploids) that originate through the functioning of 2n gametes (produced by almost all species in some frequencies) have been considered an important factor in flowering plant evolution (Osborn et al 2003;Ramanna and Jacobsen 2003;Younis et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of spontaneous triploids from crosses between diploids was reported in some plant species. Triploids of Citrus (Chen et al, 2008) and carnation (Dianthus caryophyllus L.) (Nimura et al, 2008) were derived from the fertilization of 2n (female) and n (male) gametes, whereas those of tulip (Okazaki et al, 2005) and poplar (Populus tomentosa Carr.) (Zhang et al, 2007) were from the fertilization of n (female) and 2n (male) gametes.…”
Section: Resultsmentioning
confidence: 99%